Molecular Hydrogen Reduces Electromagnetic Pulse-Induced Male Rat Reproductive System Damage in a Rodent Model. (25th September 2022) - Ma, Long; Hao, Wei; Feng, Wen-Bo; Cao, Lu-Cheng; Qin, Li-Na; Wang, Yao; Liu, Ming-Hua; Wang, Neng-Zhuang; Gao, Fu; Guo, Jia-Ming; Du, Hui; Yan, Hong-Li
Abstract : Infertility has got to be a broadly concerned social issue these days, in which the malefactor cannot be overlooked. Numerous studies have shown that electromagnetic pulse (EMP) radiation may have seriously damaging effects on reproductive health, through nonthermal effects and oxidative stress. Molecular hydrogen, a selective hydroxyl radical scavenger, explains the protective effects against many diseases closely associated with oxidative damage, such as ionizing radiation (IR). We sought to characterize the beneficial effects of molecular hydrogen on the male reproductive system in a rodent EMP exposure model. The 8-week-old male Sprague-Dawley rats were exposed to EMP (peak intensity 1000 kV/m, pulse edge 20 ns, pulse width 200 ns, 1 Hz, and 200 pulses), with or without hydrogen-rich water. The pathological structure of the testis, the rate of apoptosis of the testis, the serum testosterone level, the sperm parameters, and the activity of the antioxidant enzymes of the testis were measured. Then, transcriptomic and untargeted metabolomic analyses were applied to uncover the underlying mechanism. Exposure to EMP increased testicular apoptosis rate and apoptosis protein level, decreased sperm viability and motility, decreased serum testosterone levels, and diminished testicular antioxidant capacity. Molecular hydrogen-alleviated damage decreased the testicular apoptosis rate and apoptosis protein level, increased sperm motility, increased serum testosterone levels, and improved antioxidative capacity. Omics results showed that molecular hydrogen has a strong influence on metabolic pathways, and EMP affects mainly oxidative phosphorylation, TNF signaling pathways, and cytokine-receptor interactions. The mechanism of molecular hydrogen's effect may be related to the reversal of some metabolite levels. These observations warrant molecular hydrogen as an innovative approach for potential protection against EMP.